Impact of an early-exposure geriatrics curriculum in an accelerated baccalaureate-MD program. Issue 4 (1st October 2020) - Hagiwara, Yuya; Pagan-Ferrer, Juan; Sanchez-Reilly, Sandra
ABSTRACT: Current standard geriatric curricula and exposure of students to the elderly may be insufficient to influence students' interest in geriatric medicine. We developed an innovative curriculum to address this gap. This study aimed to identify knowledge, skill, and attitude changes of first-year students in an accelerated baccalaureate-MD program toward geriatrics after participation in an early-exposure geriatrics curriculum (GC). The GC consisted of fifteen 3-hr interactive teaching sessions facilitated by various health professionals. This was a single group, pre- and post-intervention study using a knowledge test and attitude survey. To assess the effectiveness of this curriculum, students also completed an Objective Structured Clinical Exam (OSCE) on falls, cognitive and functional assessment, and delivering bad news. Twenty-seven baccalaureate-MD students (mean age = 18.8 years) participated in the GC intervention between January and April 2015. The post-GC showed significant improvement in knowledge ( P = 0.013), skills, and attitude ( P < 0.01) toward older adults. Students as a group overall met the standard of 85% of possible points in all three OSCE cases. This study shows that an early-exposure geriatric education intervention is associated with an increase in students' knowledge, skills, and attitudes in caring for older adults.